Pengembangan Aplikasi Integrasi Web pada Toko Buku Online - , YOHANES PRIYO ATMOJO; , Widyawan, S.T, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Online bookstores offer convenience for site visitors to see the stock of books from the bookstore without having to come into the bookstore directly, simply by visiting the online bookstore. With a variety of convenience provided by online bookstores,users can easily find the desired book. But what if an online bookstore does not have the book the customer wants, or the book is unavailable, then the customer will have to repeat the search process at other online book stores and it means adding searching time. In addition, online bookstore does not have integration between each other, it harder people to discover books comparison. Related to that case, there are some interesting questions: How to gather book data from each online bookstores, and how to store and combine the data from each sources into the database so it can be used as reference for searching books which involves several online bookstores, so make it easier for visitors to find the book they are looking for. In this thesis,the researchers tried to create a web system that can perform the integration of data from several online bookstore by using DOM characteristic from each bookstore. The process of merging data from several online bookstores, using the principle of ETL (Extract, Transform and Load) on the data which will then serve as a copy of the sources used, so that data retrieval will be faster because the only access to the internal database of system web integration.